Charles-Étienne Brasseur de Bourbourg, premier grand mayaniste de France - Lebon, Jean-Marie, (Archaeological lives., 2015)
200 years ago, on September 8, 1814, in the northern French city of Bourbourg, a boy was born into a family of local entrepreneurs connected to the local political or judicial elite. The young Charles-Etienne Brasseur was lucky to spend days and days in the impressive library of Alexandre Nicolas Muchembled, the son of his godmother. The reading of exciting travel books there mapped out the course of his truly adventurous life to come. Although a rebellious schoolboy, he acquired a huge knowledge in many fields by his omnivorous reading of books and journals. He was also a very curious young man, delving into the private libraries of the local grand families, resulting in him contributing many historical articles to newspapers and learned societies. At the age of 24, while still in high school, he published his first novel. This text tells his story.